Asymmetric Stepwise Reductive Amination of Sulfonamides, Sulfamates, and a Phosphinamide by Nickel Catalysis. (5th December 2018) - Zhao, Xiaohu; Xu, Haiyan; Huang, Xiaolei; Zhou, Jianrong Steve
Abstract: Asymmetric reductive amination of poorly nucleophilic sulfonamides was realized in the presence of nickel catalysts and titanium alkoxide. A wide range of ketones, including enolizable ketones and some biaryl ones, were converted into sulfonamides in excellent enantiomeric excess. The cyclization of sulfamates and intermolecular reductive amination of a diarylphosphinamide were also successful. Formic acid was used as a safe and economic surrogate of high‐pressure hydrogen gas.